Hubungan Fungsi Kepemimpinan Kepala Ruangan Dengan Kinerja Perawat Dalam Penerapan Keselamatan Pasien di Ruang Rawat Inap RSU GMIM Pancaran Kasih Manado - Eka Silfani Adnan; Silvia Dewi Mayasari Riu; Bayu Dwisetyo (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2023)
An effective leader is a prerequisite for determining safe treatment. The factor that affects the performance of nurses in the implementation of patient safety is leadership. The leadership role in improving patient safety in particular encourages and guarantees the implementation of patient safety programs in an integrated manner. Objective: To know the leadership functions of the chief of the room with the performance of nurses in the application of patient safety in the hospital room at RSU GMIM Pancaran Kasih Manado. Type of research: using descriptive analytical research methods with cross sectional approaches. The population of this research taken 115 population, The sample were 35 peoples using random sampling technique. Using the Chi-Square Statistical Test with a level of prosperity α ≤ 0,05. Result: Obtained a p=0,000 (α ≤ 0.05) ) that means there is a relationship between the function of the head of the chamber and the performance of nurses in the implementation of patient safety in the hospital's nursing room.The conclusion in this is that there is a link between the leadership function on the chief of the room and the performance of nurses in the application of patient safety in the Hospital Room of the RSU GMIM Pancaran Kasih Manado. The advice is expected to be the evaluation material for the future in order to create quality of nursing services.